Dari Lapangan Terbang Tradisional Hingga Bandara Internasional: Sejarah dan Perkembangan Bandara - Rafli Ahmad Ramadhan; Dedi Irwanto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this study is to analyze the history of Sultan Mahmud Badaruddin II Airport in Palembang, which has a long history dating back to the Dutch colonial era as Talang Betutu Airport and continues to develop into an international airport. This study uses a historical research methodology consisting of four stages: heuristics, criticism, interpretation, and historiography. The results of the study indicate that the role of SMB II Airport continues to develop from its initial role as a traditional airfield, military base, civil airport, airport, to an international airport. Since becoming an international airport, SMB II Airport has been integrated with the development of airport facilities and the provision of modern mass transportation such as LRT, contributing significantly to increasing the efficiency of the transportation system, local economic growth, and development progress in South Sumatra. In conclusion, Sultan Mahmud Badaruddin II Airport not only functions as an air transportation facility but also plays a strategic role as a driver of regional development and regional connectivity in South Sumatra. Keywords: Airfield, International Airport, Military Base Port, Talang Betoetoe, Sultan Mahmud Badaruddin II.